Crusade in Europe - Eisenhower, Dwight D., 1890-1969 (Garden City, New York Doubleday and Company, 1948)
Within the pages of this book the single most important military figure of World War II has written the story that is destined to become the single most important record of that conflict. Here, from the hand of the Supreme Commander of the Allied forces, is the complete story of the war as Eisenhower planned it and lived it. Through his eyes you can now see the whole gigantic drama of the war -- the strategy, the battles, the moments of fateful decision. Yet this is a warm and richly personal account. No personality among all those described is more clearly defined than that of Eisenhower himself. Through his own account of the long months of waiting and planning and working, through his description of the gradual formation of the great plans for victory, through his record of the history-making hours when the machinery of battle had been launched and could no longer be recalled, you come to know this great man as no one else could describe him to you.
Include Footnotes, Appendix, Glossary and Index
Keywords: World War (1939-1945) -- Military campaigns -- Eisenhower, Dwight D. (Dwight David), 1890-1969 -- United States